Dayak Students’ Attitude toward Bilingualism in West Kalimantan Indonesia - Rizqi, Muhammad Ainur (Indonesian Journal of EFL and Linguistics, 2017)
Amid many studies investigating language attitudes, very few studies placing their emphasis on attitudes toward bilingualism. This study sets out to examine how Dayak students react toward two languages (i.e. Indonesian and Dayak Language) that have existed in their surrounding for quite a long time. This study was quantitative in nature, despite containing some elements of qualitative data. The study employed questionnaires that consisted of 20 main questions and 1 open-ended question. The questionnaires then were distributed online to 32 Dayak students studying in university with various discipline backgrounds. The results indicate that Dayak students in this study share a positive attitude toward bilingualism, although the rate varies if we investigate the smaller components of the attitudes. It is reported that the students are very positive in a surficial level of attitudes (i.e. cognitive components), yet slightly low in emotional dimensions (i.e. affective components). Further, the students also seem doubtful to implement their belief and feeling into real action, for example in education (i.e. readiness for action). This paper concludes by summarising key findings and acknowledging research limitations, especially concerning with generalisability and participant’s sociolinguistic aspects.